2013
DOI: 10.1107/s1600536813015389
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminopyridin-1-ium triiodide

Abstract: The asymmetric unit of the title compound, C5H7N2 +.I3 −, consists of one 2-amino­pyridin-1-ium cation (apyH+) and one triiodide anion, both located in general postions. The apyH+ cation is planar within the experimental uncertainties. The short N—C distance [1.328 (5) Å] of the exocyclic NH2 group is typical for the imino-form of protonated 2-amino­pyridines. Consequently, the bond lengths within the six-membered ring vary significantly. The geometric parameters of the triiodide anion are in the typical range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Especially the semi-flexible a,w-diazaniumalkane cationsassistedthe synthesisofaseries of new polyiodides [5,1 5-18]. This contribution is part of our general interest in the hydrogen bonding topologies of aminopyridinium salts [19] and of our attempts to synthesise polyiodides using simple N-heterocyclic cations [20][21][22]. The asymmetric unit of the title structure consists of four crystallographically independent 4-aminopyridin-1-ium cations, two iodide and two triiodide anions.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the semi-flexible a,w-diazaniumalkane cationsassistedthe synthesisofaseries of new polyiodides [5,1 5-18]. This contribution is part of our general interest in the hydrogen bonding topologies of aminopyridinium salts [19] and of our attempts to synthesise polyiodides using simple N-heterocyclic cations [20][21][22]. The asymmetric unit of the title structure consists of four crystallographically independent 4-aminopyridin-1-ium cations, two iodide and two triiodide anions.…”
Section: Discussionmentioning
confidence: 99%
“…We have already shown that heterocyclic cations like pyridinium derivatives [22,23] or naturally occurring bases like caffeine [24] are excellent educts for the synthesis of polyiodide containing salts. In particular, there is profound interest in the competition between hydrogen and halogen bonding in haloanilinium halogenides [25,26].…”
Section: Commentmentioning
confidence: 99%
“…Stacking of planar molecules with orientational deviations to ll the needs of packing are known well known [10].…”
Section: Atom Sitementioning
confidence: 99%